Causative organisms in microbial keratitis, their sensitivity pattern and treatment outcome in western Nepal - Dhakwa, K; Sharma, MK; Bajimaya, S; Dwivedi, AK; Rai, S KC (Nepalese Journal of Ophthalmology, 2012)
Introduction: Corneal infection is one of the major causes of monocular blindness in developing countries. Objective: To determine the epidemiological characteristics, predisposing factors, microbiological pattern, sensitivity pattern and treatment outcome of microbial keratitis. Materials and methods: A retrospective analysis of hospital records of 414 patients with diagnosed infective keratitis was done. The outcome measures were microbial isolates, their sensitivity to therapeutic agents and treatment outcome. Results: Of the total, 312 (75.4 %) patients were farmers by profession, 138 (33.3 %) had a history of ocular trauma and 17(4.1 %) were using topical corticosteroids. Among the 138 cases of the corneal ulcer with trauma, 52 (37.68 %) had fungi isolated in culture (RR=0.54, 95% CI = 0.44 – 0.68) and 32 (23.19 %) had a bacterial growth. Cultures were positive in 300 (72.5 %) cases, having 138 (33.3 %) patients with pure fungal infection, 121 (29.2 %) with pure bacterial and 41 (9.9 %) with mixed infection. Fusarium spp was the most common fungal pathogen while Staphylococcus epidermidis was the commonest bacterial isolate. The most sensitive antibiotics for the Gram positive bacteria was cephazolin (84.92 %), while for Gram negative, ciprofloxacin and ofloxacin were the most effective (79.31 %). Of 414 cases of corneal ulcers, 363 (87.7 %) cases healed completely. Conclusion: Microbial keratitis is mostly seen in farmers in this part of the world. Fusarium and Staphylococcus epidermidis were the most common isolates. Cephazoline and ofloxacin were the most effective antibiotics for Gram positive and Gram negative organisms respectively. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5863 NEPJOPH 2012; 4(1): 119-127